Coherent Radiation of Relativistic Electrons in a Wire Metamaterial; RREPS-15. Radiation from Relativistic Electrons in Periodic Structures - Soboleva V. V. Veronika Vyacheslavovna (General Aspects of Physical Phenomena and Processes Associated with Electromagnetic Radiation, 2015)
Title screen.